Effects of integrated and inquiry teaching approaches on students' achievement in secondary school economics in Ibadan metropolis (2019)
The study investigated effects of integrated and inquiry teaching approaches on students' achievement in economics in senior secondary schools. The study adopted Pre-test, Post-test Control group Quasi- experimental design. The participants comprised 108 Senior Secondary School class two (SS 2) students in three schools randomly selected from two Local Government Areas in Ibadan Metropolis. The instruments were: Economics Achievement Test (EAT) (r =0.77), Students' Attitude to Economics Questionnaire (SAEQ) (r=0.82) and Numerical Ability Test (NAT) (r=0.72). Seven hypotheses were raised and tested at 0.05 level of significance. Data were analysed using Analysis of Covariance (ANCOVA). The results revealed significant main effect of treatments (inquiry, integrated and conventional teaching approaches) [F(2. 89) = 15.53; P < 0.05], and numerical ability on secondary students' achievement in economics [F(2. 89) = 4.97; p < 0.05 while there was no significant main effect of students' attitude to economics on achievement in economics [F(2. 89) = .64; p > 0.05], Results also showed that: no significant first order interaction effect existed between treatment and numerical ability [F(4 89) = .41; p > 0.05],treatments and students' attitude to economics[F(2.89)= 1.293; P > 0.051 and between numerical ability and students' attitude to economics on students' achievement in economic[[(2.89)= .67; P > 0.05]; significant second order interaction effect was found among treatments, numerical ability and students' attitude to economics on students' achievement[F(4. 89) = 2.84; P < 0.05. The study recommended that inter-connection of subjects should be introduced in teaching economics in secondary school to arrest and sustain students' interest and attitude to economics, thereby leading to improvement in performance.